EVALUATION OF MALE REPRODUCTIVE HEALTH USING CONVENTIONAL SEMEN ANALYSIS IN THE POPULATION OF DISTRICT KARAK, KHYBER PAKHTUNKHWA, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
The evaluation of male reproductive health using traditional semen analysis is a crucial method in identifying male infertility. This approach determines a man's reproductive potential by assessing important semen factors such as sperm concentration, motility, and morphology. The aim of semen analysis in District Karak is to assess male fertility levels and identify potential reproductive health issues within the population. A cross-sectional analysis in Tehsil karak, Takht-e-Nasrati, and Banda Daud Shah assessed semen quality in 250 male patients aged 18 -60.Data was collected via semen samples obtained after 2-6 days of abstinence. Laboratory analysis evaluated semen volume, pH, color, viscosity, sperm concentration, motility, and morphology. The study analyzed 250 semen samples from male patients in district karak using WHO 2021 guidelines. The overall abnormality rate was 18%, with the highest irregularity in Tehsil Karak (20%) and the lowest in Tehsil Banda Daud Shah (14.28%).Age-wise, the highest abnormality 20% was in the 46-55 age group. Key findings showed 10% at semen volume